Immunofluorescence microscopy-based detection of ssDNA foci by BrdU in mammalian cells - Kilgas, Susan; Kiltie, Anne E.; Ramadan, Kristijan (STAR protocols, 2021)
DNA end resection converts broken ends of double-stranded DNA (dsDNA) to 3′-single-stranded DNA (3′-ssDNA). The extent of resection regulates DNA double-strand break (DSB) repair pathway choice and thereby genomic stability. Here, we characterize an optimized immunofluorescence (IF) microscopy-based protocol for measuring ssDNA in mammalian cells by labeling genomic DNA with 5-bromo-2′-deoxyuridine (BrdU). BrdU foci can be detected under non-denaturing conditions by anti-BrdU antibody, providing an accurate and reliable readout of DNA end resection in most mammalian cell lines. For complete details on the use and execution of this protocol, please refer to Kilgas et al. (2021). [Display omitted] •Single-stranded DNA (ssDNA) detection by BrdU labeling under non-denaturing conditions•Number of ssDNA foci measured by immunofluorescence (IF)-based confocal microscopy•Compatible with co-staining for cell cycle markers•Amenable to semi-quantitative image analysis for quantification DNA end resection converts broken ends of double-stranded DNA (dsDNA) to 3′-single-stranded DNA (3′-ssDNA). The extent of resection regulates DNA double-strand break (DSB) repair pathway choice and thereby genomic stability. Here, we characterize an optimized immunofluorescence (IF) microscopy-based protocol for measuring ssDNA in mammalian cells by labeling genomic DNA with 5-bromo-2′-deoxyuridine (BrdU). BrdU foci can be detected under non-denaturing conditions by anti-BrdU antibody, providing an accurate and reliable readout of DNA end resection in most mammalian cell lines.